2012
DOI: 10.1186/1477-7819-10-161
|View full text |Cite
|
Sign up to set email alerts
|

The correlates of benefit from neoadjuvant chemotherapy before surgery in non-small-cell lung cancer: a metaregression analysis

Abstract: BackgroundAlthough neoadjuvant chemotherapy (NCT) is widely used, it is not clear which subgroup of locally advanced non-small-cell lung cancer (NSCLC) patients should be treated with this approach, and if a particular benefit associated with NCT exists. In this study, we aimed to investigate the potential correlates of benefit from NCT in patients with NSCLC.MethodsAll randomized clinical trials (RCTs) utilizing a NCT arm (without radiotherapy) versus a control arm before surgery were included for metaregress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…NT can reduce or eliminate the micro-metastasis especially in patients with advanced lung cancer (4,5). Recent systematic reviews have integrated the previously published randomized control trials (RCTs) and concluded that NT can significantly benefit the survival outcomes of operable patients (4)(5)(6). However, the impact of NT on intraoperative and postoperative complications still remains a debate (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NT can reduce or eliminate the micro-metastasis especially in patients with advanced lung cancer (4,5). Recent systematic reviews have integrated the previously published randomized control trials (RCTs) and concluded that NT can significantly benefit the survival outcomes of operable patients (4)(5)(6). However, the impact of NT on intraoperative and postoperative complications still remains a debate (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the statistical methods of evidence-based medicine (EBM) which are represented by meta-analyses, have been increasingly applied in clinical practice to draw relatively global conclusions by quantitatively integrating the appropriate data from homogeneous studies (4)(5)(6)14). The current evidences revealing the effects of NT on BPF risk have not yet been systematically reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Now there are new treatment options, especially for patients in advanced stages. For example, preoperative chemotherapy or the tyrosine‐kinase inhibitor erlotinib can be used in some patients to prolong survival …”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant chemotherapy following surgically resected (Stage IB (> 4 cm)-IIIA) NSCLC is now considered the standard of care, but the neoadjuvant setting is less well established. Neoadjuvant chemotherapy (NAC), which is defined as chemotherapy applied before surgery, has been investigated by various trials [ 8 18 ] and systematic reviews [ 19 , 20 ], with controversial results; some reported survival benefit with improved resection rate and micro-metastasis control. Since many of the studies included in the previous meta-analyses [ 19 , 20 ] were non-randomized small-scale trials, the results were unconvincing with biases.…”
Section: Introductionmentioning
confidence: 99%